Metabolic Changes After a 24-Week Soccer-Based Adaptation of the Diabetes Prevention Program in Hispanic Males: A One-Arm Pilot Clinical Trial - Frediani, Jennifer K.; Li, Jianheng; Bienvenida, Alan; Higgins, Melinda K.; Lobelo, Felipe (Frontiers in Sports and Active Living, 2021)
Aims: One third of the U.S. adult population is estimated to have obesity-associated prediabetes. Hispanics have a 50% higher type 2 diabetes death rate compared to non-Hispanic whites, yet low participation in lifestyle change programs, making this subgroup an important target for prevention. Our objective was to determine the feasibility and the effects of an intervention implementing the Center for Disease Control and Prevention National Diabetes Prevention Program (NDPP) plus recreational soccer (RS) in Hispanic men. Methods: Overweight and obese Hispanic men, aged 30-57 years with prediabetes at screening were recruited (n=41). Trained soccer coaches led 30-minute facilitated discussion of the NDPP modules after each RS session, with two sessions per week for 12 weeks and once per week for the following 12 weeks. The 1-hour RS sessions followed the Football Fitness curriculum. Assessments included body mass index, waist circumference, bioelectrical impedance analysis (InBody 270), blood pressure, glycated hemoglobin (HbA1c), and validated physical fitness tests. Multilevel mixed models assessed the outcomes as a function of time and cohort and incorporated an unstructured covariance structure to examine the changes from baseline to 24 weeks. All analyses were conducted as intent-to-treat using SAS v 9.4. Results: Hispanic males (n=41; mean age 41.7 [0.1] years) were obese at baseline (mean BMI 32.7, standard error of mean [0.7], mean weight 93.9 [2.2] kg). Attendance rate was 65% overall at 12 weeks but differed between cohorts. Five mild injuries occurred over the trial. After 24 weeks of the NDPP+RS intervention, there were significant decreases in systolic and diastolic blood pressure (%change -4.7[SE 2.4]; 95% CI [-11.5, -1.7] and -6.1 [1.7] mmHg; [-9.6, -2.6], respectively), HbA1c (-0.2 [0.1]; [-0.3, -0.1]), Despite significant reductions in weight (-3.8 [0.7]; [-5.2, -2.5]), waist circumference (-6.6 [0.7] cm; [-8.0, -5.1]), body fat % (-1.9 [0.5]; [-2.8, -1.0]), lean body mass was preserved (-0.9 [0.3]; [-1.6, -0.2]). Conclusion: A 24-week soccer-based adaptation of the Diabetes Prevention Program is safe and feasible among middle-aged Latino men.